Tradeoff between Intermolecular Interaction and Backbone Disorder by High Molecular Dipole Block for Improving Blend Morphology of Polymer Solar Cells. (3rd October 2022) - Yang, Tongyan; Liao, Chentong; Duan, Yuwei; Xu, Xiaopeng; Deng, Min; Yu, Liyang; Li, Ruipeng; Peng, Qiang
Abstract: Constructing terpolymer has attracted increasing attention as a strategy to improve the performance of polymer solar cell. Terpolymer usually offers an opportunity to lower the frontier molecular orbital energy level, introduces additional absorption band and sometimes optimizes the morphology of the active blend. Generally, the additional segment in terpolymer backbone inevitably introduces backbone disorder, which causes entropy rises. However, selecting a suitable dipole unit introduces extra driving forces for crystallization by enhancing intermolecular interactions. This provides a handy knob for tradeoff between intermolecular interaction and backbone disorder, thus regulating the blend morphology. Herein, a high dipole and electron‐deficient group of pyrrolo[3, 4‐f]benzotriazole‐5, 7(6H)‐dione (TzBI) is incorporated into the high‐performance donor polymer and a series of terpolymers with different content of TzBI are designed. As expected, the morphology is optimized gradually for improving charge generation and charge transport, also suppressing charge recombination. The champion device with 10% TzBI exhibited a power conversion efficiency (PCE) of 18.36%, which is 5% increase compared to the controlled device. This study presents a charming terpolymer strategy by highly electron‐deficient and high dipole segment to realize a tradeoff between intermolecular interaction and backbone disorder, facilitating the optimization of morphology and elevation of fill factor and device efficiency. Abstract : A novel but efficient terpolymer strategy by introducing highly electron deficient pyrrolo[3, 4‐f]benzotriazole‐5, 7(6H)‐dione block with high molecular dipole resolves the tradeoff between intermolecular interaction and backbone disorder well, facilitating the optimization of blend morphology and elevating the fill factor and power conversion efficiency to a high level.